High-Throughput MicroRNA and mRNA Sequencing Reveals That MicroRNAs May Be Involved in Melatonin-Mediated Cold Tolerance in Citrullus lanatus L. - Li, Hao; Dong, Yuchuan; Chang, Jingjing; He, Jie; Chen, Hejie; Liu, Qiyan; Wei, Chunhua; Ma, Jianxiang; Zhang, Yong; Yang, Jianqiang; Zhang, Xian (Frontiers in Plant Science, 2016)
Transcriptional regulation of cold-responsive genes is crucial for exogenous melatonin-mediated cold tolerance in plants. Nonetheless, how melatonin regulates cold-responsive genes is largely unknown. In this study, we found that exogenous melatonin improved cold tolerance in watermelon by regulating expression of microRNAs (miRNAs). We identified a set of miRNAs that were regulated by melatonin under unstressed or cold conditions. Importantly, mRNA-seq analysis revealed that melatonin-induced downregulation of some miRNAs, such as miR159-5p, miR858, miR8029-3p, and novel-m0048-3p correlated with the upregulation of target genes involved in signal transduction (CDPK, BHLH, WRKY, MYB, and DREB) and protection/detoxification (LEA and MDAR) under cold stress. These results suggest that miRNAs may be involved in melatonin-mediated cold tolerance in watermelon by negatively regulating the expression of target mRNAs.